Anticancer 4: Anticancer and DNA cleavage studies of some new Schiff base titanium (IV) complexes - El-Shekeil, Ali Gumaan; Abubakr, Abeer Omer; Al-Aghbari, Sama Abdalla; Nassar, Mogahid Yahya (European Journal of Chemistry, 2014)
Two metal complexes of Ti(IV) were synthesized with newly prepared biologically active ligands. These ligands and their functional groups were carefully designed and selected from well known anticancer drugs. The ligands were prepared by the condensation of a mixture of sulfamethoxazole and the appropriate aldehyde namely, 3,4-dimethoxybenzaldehyde and 3,4,5-trimethoxybenzaldehyde. The structure of the ligands and their complexes were confirmed by spectroscopic data i.e. IR, 1H NMR,electronic and elemental analysis. All compounds were screened for their in vitro anticancer potential using HELA and PC3 cells. All compounds showed limited cytotoxicity and complete cleavage of calf thymus deoxyribonucleic acid (CT-DNA).